1998
DOI: 10.1046/j.1365-2133.1998.02070.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcipotriol monotherapy and a combination of calcipotriol and betamethasone valerate after 2 weeks' treatment with calcipotriol in the topical therapy of psoriasis vulgaris: a multicentre, double‐blind, randomized study

Abstract: A clinical study was conducted to determine whether, in the topical treatment of psoriasis, a combination of calcipotriol and betamethasone valerate after previous treatment with calcipotriol alone was more effective than the continuation of the monotherapy with calcipotriol, especially in 'low responders'. Patients (n = 169) with the clinical diagnosis 'chronic plaque-type psoriasis' were treated twice daily for 2 weeks with calcipotriol, followed by a 4-week treatment with calcipotriol monotherapy in 87 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 17 publications
2
42
0
8
Order By: Relevance
“…Although these compounds have not been assayed in the treatment of IBD, they were shown to be effective in small open label trials in psoriasis and rheumatoid arthritis. [132][133][134][135] Heliotherapy also increases serum vitamin D concentrations. Exposure of a human body in a bathing suit to one minimal erythema dose of sunlight has been reported to be equivalent to ingesting about 10 000-25 000 IU of vitamin D. 136 In a single case report, a CD patient exposed to a tanning bed (UVB radiation 290-315 nm) while wearing a one-piece bathing suit for 10 minutes per day, 3 times per week for 4 weeks experienced an increase in serum 25(OH) D concentration from 7 to 32 ng/mL.…”
Section: Form Of Administrationmentioning
confidence: 99%
“…Although these compounds have not been assayed in the treatment of IBD, they were shown to be effective in small open label trials in psoriasis and rheumatoid arthritis. [132][133][134][135] Heliotherapy also increases serum vitamin D concentrations. Exposure of a human body in a bathing suit to one minimal erythema dose of sunlight has been reported to be equivalent to ingesting about 10 000-25 000 IU of vitamin D. 136 In a single case report, a CD patient exposed to a tanning bed (UVB radiation 290-315 nm) while wearing a one-piece bathing suit for 10 minutes per day, 3 times per week for 4 weeks experienced an increase in serum 25(OH) D concentration from 7 to 32 ng/mL.…”
Section: Form Of Administrationmentioning
confidence: 99%
“…Treatment with the combination ointment gives relevant advantages also in terms of patient's compliance, thanks to the once-daily application, quality oflife parameters and tolerability profile (5-10). The use of combination product may reduce the risk of adverse events associated with the long-term use of corticosteroid monotherapy (atrophy and rebound) as well as the irritation associated with calcipotriol (18,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy is as high as moderately potent steroids [4, 9]. The combination of calcipotriol with steroids further increases the effectiveness of the therapy, due to synergistic effects of the drugs [11,12,13,14,15]. The once daily application of calcipotriol and betamethasone dipropionate as a 2-compound product could offer an even higher effectiveness and cost-effectiveness compared to a twice daily application of the respective compounds, due to a higher compliance, enhanced synergistic effects and lower treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…Betamethasone dipropionate, a group III corticosteroid, acts via a glucocorticoid receptor and suppresses inflammation and hyperproliferation [10]. Several studies have shown that the combination of these 2 reagents has synergistic or additive effects and is better tolerated than either monotherapy [11,12,13,14,15]. In addition, the long-term safety of a fix calcipotriol/betamethasone dipropionate combination (Daivobet®/Dovobet®/Taclonex®) has been evaluated positively in several studies [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%